2022
DOI: 10.1037/vio0000413
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a youth-led sexual violence prevention program among adolescents: The impact of engagement.

Abstract: Objective: Most studies of peer sexual violence (SV) prevention programs for adolescents focus on program outcomes or feasibility and acceptability; few examine how exposure levels or dosage affects impact. The present study examined the effects of attending multiple community-located youth-led prevention events, as compared to attending one or none, on peer violence (PV)-related attitudes and behaviors. Method: Middle and high school students (M age at first wave = 13.7; 53.2% female; 76.5% White; 21.0% Nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…These data are part of a larger multiple baseline study to evaluate a youth-led sexual violence prevention project (Banyard et al, in press; Edwards et al, 2021b; Waterman et al, 2021). These data come from a survey administered between February and April of 2020 and was completed by caregivers of youth who participated in Youth VIP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are part of a larger multiple baseline study to evaluate a youth-led sexual violence prevention project (Banyard et al, in press; Edwards et al, 2021b; Waterman et al, 2021). These data come from a survey administered between February and April of 2020 and was completed by caregivers of youth who participated in Youth VIP.…”
Section: Methodsmentioning
confidence: 99%
“…Results from papers presenting youth outcomes showed that Youth VIP had some promising but mixed effects. Overall, results suggested that youth who were directly involved in Youth VIP through retreats and afterschool activities subsequently reported less perpetration of some aggressive behaviors, improvements in prevention attitudes, and more helpful active bystander behaviors to prevent peer sexual violence (Banyard et al, in press; Edwards et al, 2021b). Furthermore, when comparing youth in the same grades before and after programming, rates of violence decreased during the project period in the entire population of students (Waterman et al, 2021).…”
mentioning
confidence: 99%
“…Furthermore, given the large presence of Native American youth in the community in which the initiative took place, Lakota culture and traditions were integrated throughout various programming components. For further details, including results, see Banyard et al (in press) and Edwards et al (in press).…”
Section: Methodsmentioning
confidence: 99%
“…For example, events included things like Lakota elders as guest speakers, talking circles, smudging, making talking sticks, and discussions about the impacts and trauma of colonization on Lakota people. For more details on Youth VIP, see (Banyard et al, in press; Edwards et al, in press; Waterman et al, 2021; YouthProject, 2021).…”
Section: Researcher Positionalitymentioning
confidence: 99%